Bring it! : the revolutionary fitness plan for all levels that burns fat, builds muscle, and shreds inches - Horton, Tony (Anthony Sawyer), 1958- (Rodale Books : Distributed to the trade by Macmillan, 2011)
Creator of the best-selling P90X® workout series, Tony Horton shows you how to attain the results you want. In his first book he shares the fundamentals of his fitness philosophy, revealing his secrets for getting fit and healthy and melting away pounds. One-size-fits-all diets and exercise regimens just don't work--that's why Tony creates unique programs for each of his clients. Here he shows you how to build your own diet and fitness plan tailored to your individual lifestyle, preferences, and goals. In photographs and easy-to-follow instructions, Tony demonstrates his unique moves and exercise combinations that include cardio fat burners, lower body blitzers, core strengthening, plyometrics, yoga, and more. You'll also discover Tony's fat-blasting eating plan and detox tips, recipes, and mental motivators.--From publisher description.